Job Satisfaction, Work Values, and the Job-Hopping Trend Among Millennial Hotel Employees in Badung: the Mediating Role of Employee Engagement - I Gusti Ayu Putu Cantika UDAYANI; I Made SARA; Ni Luh Putu INDIANI (International Journal of Environmental, Sustainability, and Social Science, 2025)
The proportion of the workforce is more dominant in the millennial generation compared to the generation X and the baby boomers. The results of the 2019 Indonesian Millennial Survey by the IDN Research Institute found that the millennial generation has the lowest level of loyalty to the company and plans to stay in one company for only two to three years. This condition shows that the job-hopping behavior of the millennial generation is higher. This study aims to determine and analyze the effect of job satisfaction and work value on employee engagement and job-hopping in millennial employees in the hospitality sector in Badung Regency. As well as to determine and analyze the mediating role of employee engagement on the effect of job satisfaction and work value on JobJobJobJobJob hopping in millennial employees in the hospitality sector in Badung Regency. The population of this study was all millennial employees working in Badung Regency. The sample used was determined by indicator parameters with a minimum sample of 80 and a maximum sample of 160 respondents from millennial employees working in Badung Regency. The data collection method was a questionnaire. The analysis technique used to answer the hypothesis was inferential analysis using Partial Least Squares (PLS). The study found that job satisfaction and work value positively impact employee engagement and negatively affect job hopping. Employee engagement negatively influences job hopping and partially mediates the effects of job satisfaction and work value on job hopping.